School Leaders’ Perceptions of Teaching and Learning Science and Mathematics in a Non-native Language in Lebanon - Zaatari, Sally (2022)
This study explored the school leaders’ perceptions of teaching and learning science and mathematics in a non-native language in Lebanon. The theoretical framework was based upon four main components derived from the literature: (1) The impact of teaching and learning science and mathematics in a non-native language on the academic and linguistic performance of learners, (2) the global and sociopolitical perspectives of using a non-native language as the medium of science and mathematics instruction, (3) the influence of the latter on the cultural identity and the native language, and (4) its influence on the acquisition of science and mathematics literacy. The study used grounded theory as its methodology. Data sources included a questionnaire and individual interviews with twenty-eight school leaders in public, private, and private-free schools in Beirut, Lebanon. Coding followed by categorizing the data led to five emergent themes. The school leaders mostly preferred the use of English or French as the medium of science and mathematics instruction in Lebanon. They highlighted the controversial aspect of the influence of teaching and learning science and mathematics in a non-native language on the cultural identity and the native language. They also emphasized their role in multilingual contexts and the need for language proficiency in the acquisition of scientific and mathematical literacies. They finally explained how the use of Arabic can facilitate or hamper the teaching and learning of science and mathematics in a non-native language.